Sustainable production of hydrogen via steam reforming of furfural (SRF) with Co-catalyst supported on sepiolite. (13th May 2021) - Sayas, S.; Da Costa-Serra, J.F.; Chica, A.
Abstract: Natural sepiolite is a mineral very abundant in Spain, being the main producer worldwide. This material is presented by the first time as promised support to prepare cobalt catalysts with high activity and hydrogen selectivity in the steam reforming of furfural (SRF). Two methods for cobalt incorporation on natural sepiolite, precipitation (PP) and incipient wetness impregnation (IWI), are explored and their influence in the preparation of catalysts highly active and selective in the SRF is studied. PP method makes possible to synthesize a catalytic material with high catalytic performance (high conversion of furfural, > 95%, and high hydrogen selectivity, 70%). Furthermore the production of non-desired byproducts such as CO, CH4 and acetone, decrease significantly in the catalyst prepared by PP (CoSep). Characterization by N2 adsorption-desorption to determine surface area, XRD, TPR and TEM shows that PP method favors the formation of smaller metallic particles of Co with a high dispersion. These differential physicochemical properties seem to explain the better catalytic performance exhibited by the sepiolitic catalyst prepared by the PP method (CoSep). In addition, this catalyst exhibits also a higher resistance to deactivation after 24 h of reaction time. This fact seems to be related to the lower coke deposition on the catalyst prepared by precipitation and particularly, with the lower sinterization of the metallic Co particles during the steam reforming of furfural. Highlights: Sepiolitic Co-catalysts have been prepared for steam reforming of furfural (SRF). High furfural conversion and H2 selectivity is exhibited by sepiolite-based catalysts. Two methods to incorporate Co in the sepiolitic support has been studied for SRF. CoSep catalyst exhibited the highest catalytic performance and stability. Smaller metallic Co particles highly disperse justify the excellent results.